A complicated abscess from a dropped gallstone. Issue 11 (4th November 2019) - Murphy, Serena; Hebert, James; Leavitt, Bruce
Abstract: Laparoscopic cholecystectomies represent one of the most common procedures of General Surgery. Dropped gallstones during laparoscopic cholecystectomy is a rare occurrence but can potentially lead to morbid complications. We present a rare case of a broncho-pleuro-cutaneous fistula in a patient with recurrent abscess formations after an elective laparoscopic cholecystectomy. The fistula formed over 3 years from a gallstone that eroded through the diaphragm, into the pleural space, and eventually into a terminal bronchiole. Bilirubin staining within the fistula tract was confirmed on hematoxylin and eosin staining.